2019
DOI: 10.21608/omx.2018.4857.1014
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Rhombic Three Dimensional Plate in Fixation of Displaced Low Subcondylar Mandibular Fractures

Abstract: The aim of this study was to evaluate the rhombic three-dimensional plate in fixation of displaced low subcondylar mandibular fractures clinically and radiographically. MATERIALS AND METHODS: This is a prospective, interventional, single armed case series study that was carried out on twelve patients with displaced low subcondylar mandibular fracture. Open reduction and internal fixation was utilized to treat those fractures using rhombic 3D plate, patients were collected from the department of Oral and Maxill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
(22 reference statements)
2
1
0
Order By: Relevance
“…The results of our study give a great support to those of a recent study done in 2018, by Mahmoud F.et al, (37) who evaluated the efficiency of application of the 3D Rhombic plates in the fixation of displaced low subcondylar fractures and concluded that the 3D Rhombic plates were compatible for treatment of condylar fractures and provided satisfactory stable fixation. (38) in 2018 in their prospective randomized controlled clinical trial compared the outcomes of the 3D rhombic plates with the 2.0 miniplates in management of subcondylar fractures.…”
Section: Meyer Et Al In 2007supporting
confidence: 90%
See 1 more Smart Citation
“…The results of our study give a great support to those of a recent study done in 2018, by Mahmoud F.et al, (37) who evaluated the efficiency of application of the 3D Rhombic plates in the fixation of displaced low subcondylar fractures and concluded that the 3D Rhombic plates were compatible for treatment of condylar fractures and provided satisfactory stable fixation. (38) in 2018 in their prospective randomized controlled clinical trial compared the outcomes of the 3D rhombic plates with the 2.0 miniplates in management of subcondylar fractures.…”
Section: Meyer Et Al In 2007supporting
confidence: 90%
“…(11,17,18) Regarding mandibular movements concerning the MMO, ipsilateral, contralateral and protrusive excursions, were satisfactory in all patients of both groups and were regained gradually throughout the follow-up intervals with no statistically significant differences and gives a great support and similarity to that reported in the available literature. (34)(35)(36)(37)(38) In the present study, the Mandibular mobility in-dex and the Helkimo index of mandibular dysfunction showed superior results in the trapezoidal plate group compared to the mini-plates group (P=0.303 and P = 0.528 respectively) and both groups showed a significant improvement by time. Although the difference between groups was statistically insignificant, these results provide superiority for the single trapezoidal plate regarding the rigidity of fixation and postoperative fracture stability.…”
Section: Discussionsupporting
confidence: 48%
“…[ 1 2 ] Injury to the condylar region deserves special consideration apart from the rest of the mandible because of its unique anatomy and healing potential. [ 3 ]…”
Section: Introductionmentioning
confidence: 99%